(untitled) (Journal of Entrepreneurship and Business, 2021)
– Recently, social networking sites (SNSs) experienced increased popularity, becoming one of the most significant tools in the present high-tech world. Users can instantly interact with each other by using social media platforms, forming professional connections, friendships, and business opportunities. Nonetheless, users impact trust when using SNSs, which is the most essential component in human connection. The study aims to investigate the impact of users’ trust in using SNSs. Accordingly, 110 valid survey questionnaires were distributed through Google Form. The descriptive statistics were applied for data analysis. The results revealed that perceived privacy, sharing knowledge, and perceived ease of use significantly and positively affected users’ trust in SNSs. The study develops the knowledge in improving trust in SNSs by extending the factors based on users’ trust in SNSs